Efforts of Children Discontinued School in Buata Village, Botupingge District, Bone Bolango Regency - Ulfa Subetan; Imam Mashudi; Fitriani Husain (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine the causes and efforts to overcome school dropouts in Buata Village, Botupingge District, Bone Bolango Regency. The method used is a qualitative method with descriptive analysis. Data collection tools are to use observation guidelines, and interviews and documentation. The results of the study are:1) the causes of children dropping out of school, characterized by poor economic conditions, low parental education levels, children's desire to help their parents work, and due to peer influence; 2) efforts to overcome school dropouts are still lacking, marked by a lack of motivation and assistance from parents in the child's learning process, lack of parental supervision and encouragement, parents also let children work to help ease the workload of parents, but parents do not indulge. children by giving excessive pocket money.